Consumer Quality Perception in Traditional Food: Parmigiano Reggiano Cheese. Issue 2 (14th March 2020) - Silvestri, Cecilia; Aquilani, Barbara; Piccarozzi, Michela; Ruggieri, Alessandro
Abstract: The paper aims to classify the quality cues and attributes of grated Parmigiano Reggiano cheese, an Italian traditional food cheese, exploring if they affect consumers' quality perceptions and expectations. Analysis is based on a questionnaire administered in hypermarkets where grated Parmigiano Reggiano is sold. A factor analysis, using varimax rotation, and a cluster analysis, were performed, using the Stata 12 software package. The clusters used were: geographical origin and packaging (cluster 1); price, brand and quality certification (cluster 2); all sensory attributes (cluster 3); and a combination of sensory attributes with price, brand, and quality certification (cluster 4). This is the first study to examine the quality cues and attributes affecting quality perception and expectations of cheese for grated Parmigiano Reggiano from a consumer perspective. It is also the first to classify cheese attributes following a quality approach, encompassing previously studied sensory and other attributes.